Effect of Communicative Approach on Proposal Writing Skills of Distance Learners at Allama Iqbal Open University Islamabad: Muhammad Samiullah, Muhammad Zaigham Qadeer (PJDOL, 2023)
The purpose of this research was to find out the effect of communicative approach on proposal/synopsis writing skills of students at Allama Iqbal Open University Islamabad as it was found from the literature that Communicative Language Teaching (CLT) had a noteworthy influence to improve proposal writing skills. The researcher used the quasiexperimental research method for this stud